Analisis Life Cycle Assessment (LCA) pada Proses Produksi Pupuk ZA II Menggunakan Metode Recipe 2016 - Saffira Arlisa Devi; Mohammad Mirwan (INSOLOGI: Jurnal Sains dan Teknologi, 2023)
The operation of the fertilizer industry can cause environmental pollution, so that preventive or preventive measures are needed aimed at controlling the remaining air emissions produced and creating alternative ways of production that are environmentally friendly. In this study, the environmental impact is determined using the life cycle assessment (LCA) method, on the products and emissions produced as well as the materials used, such as raw materials, chemicals and fuels. Environmental impact assessments were carried out using an endpoint approach using the 2016 recipe method and divided into three main categories including human health, ecosystem quality and resources. In this study, SimaPro 9.4.0.2 and Open LCA 1.11.0 software are used to determine the extent of the environmental impact of the LCA process. In the LCA results, the most important moisture category in the entire ZA II fertilizer production process is resource impact with the â€œlost fossilâ€ impact category, while the process unit that produces the highest impact value is drying and cooling. The effects seen in this unit are due to the presence of ammonia chemicals from dirt-repellent materials, the resulting ammonia and carbon dioxide emissions, and excessive electricity consumption. Therefore, it is necessary to provide alternative recommended repair programs. Alternative programs that can be used to minimize the impact include: reducing anti-caking doses, using transformers, and combining reducing anti-caking doses & using transformers.